Mutagênese nas águas da Represa Guarapiranga (São Paulo/SP): prospecção da relação com variáveis ambientais - Andrade, Priscila Sainsonas de [UNIFESP] (2021)
Aquatic environments receive a large amount of chemicals and / or biological components associated with human activities, such as sewage, agricultural residues, fertilizers, pesticides, drugs, among others. It is possible that some compounds have a mutagenic effect, becoming a public health and environmental problem. The Guarapiranga reservoir, located in the Metropolitan Region of São Paulo receives a load of nutrients such as nitrogen and phosphorus, so that its waters reach supereutrophic and hypereutrophic levels, what contributes to the growth of algal blooms, including cyanobacteria that can produce cyanotoxins with mutagenic potential. The monitoring of the quality of its waters is carried out by the Environmental Company of the State of São Paulo (CETESB), which in recent years has detected the presence of mutagenic activity in the reservoir. The present study evaluated through statistical models whether the occurrence of mutagenesis in the Guarapiranga reservoir is associated with cyanobacterial blooms. The results show that the occurrence of mutagenesis in the Guarapiranga reservoir is associated with a multifactorial scenario where cyanobacteria have a moderate correlation, not a direct relationship with mutagenesis. The cyanotoxins monitored by CETESB do not even correlate with mutagenesis events.